Strategi Pemasaran Restoran Ayam Geprek Sa’i Menurut Perspektif Etika Bisnis Islam - Zuhriyah, Aminatus; Ainol; Aqidah, Waqi’atul (SAFE-Network, 2023)
This study aims to investigate business marketing strategies from the perspective of Islamic business ethics. The marketing strategy implemented at the Ayam Geprek Sa'i Kraksaan Restaurant and Islamic business ethics are in accordance with the regulations. The research method used is a qualitative method, while the type of research is descriptive. The location of this research is at the Geprek Sa'i Chicken Restaurant. Determination of informants using purposive techniques. Data collection techniques, data reduction, data presentation, and drawing conclusions. Data validity uses triangulation techniques. Based on the results of the research, the implementation of the marketing strategy carried out by the Geprek Sa'i Chicken Restaurant is seen from the principles of Islamic business ethics which include unity in providing food menus to consumers, showing a friendly attitude and smiling. Balance, which is applied to act fairly towards consumers. Free will, namely giving customers the freedom to ask questions about things they don't understand. Responsibility, which is related to economic freedom in the principle of responsibility for truth, honesty, and wisdom in promoting the appropriate menu.